Are all adverse effects undesirable? a case of chemotherapy induced adverse effect- an exception!? - Malathi, Divyashanthi Chellathambi; Priyadharsini, Raman Palanisamy; Elango, Dhivya (International Journal of Basic & Clinical Pharmacology, 2021)
Targeted cancer therapies, a recent development in cancer chemotherapy are drugs that block the growth and spread of cancer by interfering with specific molecules which are responsible for the progression of cancer, among which tyrosine kinase inhibitors play an important role. Erlotinib is a tyrosine kinase inhibitor that targets the epidermal growth factor receptor and is a promising drug for the treatment of non-small cell lung cancers and unresectable metastatic pancreatic cancers. Adverse drug reactions are noxious and unintended responses to drugs that occur at doses normally used in man. Cancer chemotherapeutics are well known to cause a wide range of adverse effects from mild to serious ones. All anticancer drugs cause alopecia, gastrointestinal disturbances, skin and hair changes as they affect all the rapidly proliferating cells in addition to cancer cells. Erlotinib causes some less serious adverse effects, one of which is trichomegaly which is presented here in this case report. Though adverse reactions are generally undesirable, trichomegaly induced by erlotinib could be considered as a marker of good tumor response to treatment and a positive outcome. Moreover, this adverse effect could be exploited in the treatment of madarosis for which currently, treatment options are very few.